Gender Differences in Digital Literacy Among Undergraduate Students of Faculty of Education, Kogi State University: Implications For E- Resources & Library Use - Maxwell, Charity Ezinne; Maxwell, Eberechukwu Mercy (Advances in Social Sciences Research Journal, 2014)
This study investigates gender differences in the computer literacy levels among undergraduate students of Faculty of Education, Kogi State University, Anyigba. The study aimed at gender differences in digital literacy among undergraduates’ students of a state university in North Central Zone of Nigeria considering digital literacy, years of computer experience, difference in number of hours of in use per week, gender difference in use of various software, relationship between computer use and experience, deviations among gender on application and problems encountered. The study employed descriptive survey to collect data. A total of 1300 students were enrolled in 1st and 2nd year, spread across the 12 programmes run in the 5 departments of the faculty. While, the demographic characteristics of the population revealed 720 (55.05%) male for both levels and 580 (44.05%) female undergraduate students for both levels. The sample size for male was 248 and 226 was for the female students using random and purposive techniques to select. Self-constructed, and structure questionnaires was used divided into 3 sections for data collection. Findings revealed that students with computer literacy were inclined to access and use of e-resources and e-library facilities better. Moreover, differences exist in digital/computer usage and software applications. Implications of these results on students’ use of the e-resources and e-library were discussed. The study argues that although there is increased access to computers by way of the attainment of western education by more girls, there is still a noticeable gender difference in the use of computer among female students in the university. Recommendation was made to improve information literacy especially in computer literacy skills for undergraduate students.